Escins Isolated from Aesculus chinensis Bge. Promote the Autophagic Degradation of Mutant Huntingtin and Inhibit its Induced Apoptosis in HT22 cells - Sun, Yueshan; Jiang, Xueqin; Pan, Rong; Zhou, Xiaogang; Qin, Dalian; Xiong, Rui; Wang, Yiling; Qiu, Wenqiao; Wu, Anguo; Wu, Jianming (Frontiers in Pharmacology, 2020)
The pathogenesis of Huntington’s disease (HD), an inherited progressive neurodegenerative disease, is highly associated with the cytotoxicity-inducing mutant huntingtin (mHtt) protein. Emerging evidence indicates that autophagy plays a pivotal role in degrading aggregated proteins such as mHtt to enhance neuronal viability. In this study, by employing preparative high-performance liquid chromatography (pre-HPLC), ultra-high performance liquid chromatography diode-array-detector quadrupole time-of-flight mass spectrometry (UHPLC-DAD-Q-TOF-MS) and nuclear magnetic resonance (NMR), three escins, escin IA (EA), escin IB (EB) and isoescin IA (IEA), were isolated and identified from the seed of Aesculus Chinensis Bge. (ACB). After EGFP-HTT74-overexpressing HT22 cells were treated with EA, EB and IEA at safe concentrations, the clearance of mHtt and mHtt-induced apoptosis were investigated by western blotting, immunofluorescence microscopy and flow cytometry methods. In addition, the autophagy induced by these escins in HT22 cells was monitored by detecting GFP-LC3 puncta, P62 and LC3 protein expression. The results showed that EA, EB and IEA could significantly decrease mHtt levels and inhibit apoptosis in HT22 cells. In addition, these three saponins induced autophagic flux by increasing LC3II protein expression, as shown by GFP-LC3 puncta formation, and by decreasing P62 expression. Among the escins tested, EB was the best inducer of autophagy, which it activated via both the mTOR and ERK signalling pathways. Furthermore, the degradation of mHtt and the commensurate decrease in its cytotoxic effects by EA, EB and IEA were demonstrated to be closely associated with the autophagy they induced, which depended on ATG7. In conclusion, we are the first to report that the escins, including EA, EB and IEA are novel autophagy inducers that degrade mHtt and inhibit mHtt-induced apoptosis in vitro. As a result of these findings, the triterpenoid saponins in ACB might be considered promising candidates for the treatment of HD.